Monitoramento das cargas de treinamento em nadador de velocidade de elite: relato de caso - Lopes, C. R.; Moreira, A.; Braz, T. V.; Borges, T. O.; Germano, M. D.; Souza, D.; Coutts, A. J.; Aoki, M. S. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2025)
This study explored the relationship between weekly internal training loads (ITL) and the perceived recovery and performance of an elite sprint swimmer over a 10-week periodized training plan, integrating hormonal and immune responses. ITL, perceived recovery, salivary cortisol, salivary testosterone, and SIgA concentrations were quantified. Repeated-sprint ability swim tests were conducted in weeks 1 and 5. The results revealed that as ITL increased, perceived recovery scores decreased (r = -0.61). Higher ITL in the initial weeks (1, 2, and 3; ~4000 AU) correlated with elevated salivary cortisol concentrations (?% = baseline to week 3 = +65%) and a decreased Testosterone:Cortisol ratio (?%=baseline-to-week 3=-46.3%). A decline in SIgA concentration (164.6 mg·L-1, ?% baseline-to-week 7=-34.5%) following a preparatory competition preceded the onset of an upper respiratory tract infection (URTI). Repeated sprint ability increased by 6.2% (week 1 to 5), and the 10-week training plan resulted in a faster 50-m freestyle time (week 1 = 22.52 s vs. target competition = 21.84 s, Delta% = -3.0%). In conclusion, the study found that performance improvement occurred after the 10-week periodized training plan, with weekly ITL correlating with recovery status and immuno-endocrine responses. Detection of decreased SIgA post-competition preceded URTI occurrence.